Les « petits » diplômes professionnels français dans la politique éducative et sur le marché du travail - Fabienne Maillard (Les éditions de la Maison des sciences de l'Homme, 2013)
On behalf of employment trends and requirements of firms, vocational qualifications job-related to workers and employees such as the CAP and BEP are subject to constant movement of reform since around thirty years. This constant redefinition, which took the form of a devaluation followed by a revival for the CAP, and by the disappearance of the training for the BEP, however résults under the observation of the functioning of the labor market as ambiguous status conferred on these degrees. Officially dedicated to work, they are also instruments for managing the education system. In this sense, they contribute to the success of educational policy, which does not hesitate to impose their scholactic function on their professional dimension, even making them fragile on the labor market.